2004
DOI: 10.1063/1.1824898
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional theory-symmetry-adapted intermolecular perturbation theory with density fitting: A new efficient method to study intermolecular interaction energies

Abstract: The previously developed DFT-SAPT approach, which combines symmetry-adapted intermolecular perturbation theory (SAPT) with a density-functional theory (DFT) representation of the monomers, has been implemented by using density fitting of two-electron objects. This approach, termed DF-DFT-SAPT, scales with the fifth power of the molecular size and with the third power upon increase of the basis set size for a given dimer, thus drastically reducing the cost of the conventional DFT-SAPT method. The accuracy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
768
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(783 citation statements)
references
References 50 publications
9
768
0
2
Order By: Relevance
“…DFT-SAPT interaction energies are usually underestimated when using this basis set, mainly because the dispersion component is underestimated by about 10-20%. 110 This underestimation does not change the conclusions regarding the relative importance of the individual contributions to the interaction energy given below. With a larger basis set DFT-SAPT was shown to provide very accurate total interaction energies in good agreement with the most accurate CCSD(T) calculations.…”
Section: Dft-symmetry Adapted Perturbation Theory (Dft-sapt)mentioning
confidence: 94%
See 1 more Smart Citation
“…DFT-SAPT interaction energies are usually underestimated when using this basis set, mainly because the dispersion component is underestimated by about 10-20%. 110 This underestimation does not change the conclusions regarding the relative importance of the individual contributions to the interaction energy given below. With a larger basis set DFT-SAPT was shown to provide very accurate total interaction energies in good agreement with the most accurate CCSD(T) calculations.…”
Section: Dft-symmetry Adapted Perturbation Theory (Dft-sapt)mentioning
confidence: 94%
“…With a larger basis set DFT-SAPT was shown to provide very accurate total interaction energies in good agreement with the most accurate CCSD(T) calculations. 110 Using the aug-cc-pVDZ basis set for the IP calculations does not affect the shift values dramatically, and resulting errors should be smaller than the SAPT basis-setsize errors.…”
Section: Dft-symmetry Adapted Perturbation Theory (Dft-sapt)mentioning
confidence: 99%
“…38 The ab initio method used was SAPT(DFT): symmetry-adapted perturbation theory (SAPT) based on monomer wave functions, orbital energies, and response properties obtained from (time-dependent) DFT calculations. This method, initially proposed by Williams and Chabalowski, 63 was later extended and implemented by Misquitta et al [64][65][66] and by Heßelmann et al 37,67,68 It is much more economical than the regular SAPT 69 or the coupledcluster method using single, double, and perturbative triple excitations, CCSD(T), the two approaches that have established themselves currently as the most accurate of practically applicable methods for obtaining intermolecular interaction potentials. Both groups have shown that SAPT(DFT) results for the benzene dimer are about as accurate as the results from CCSD(T).…”
Section: Introductionmentioning
confidence: 99%
“…4 Further estimates of three-body lattice energy contributions using symmetry-adapted perturbation theory based on densityfunctional descriptions of the monomers [SAPT(DFT)] [5][6][7][8][9][10][11][12] for crystalline benzene indicated that three-body effects contribute around 1.6 kcal mol −1 (or about 14% of the total lattice energy). 13 More recent studies 14,15 suggest that the majority of the three-body effects in crystalline benzene are due to three-body dispersion interactions, estimated to contribute 1.1 or 1.7 kcal mol −1 using the Axilrod-Teller-Muto expression (below).…”
Section: Introductionmentioning
confidence: 99%